Achieving Sustainable Food Systems in a Global Crisis - de Brauw, Alan; Bizikova, Livia; Picard, Francine; Smaller, Carin (2023)
Presentation by Alan de Brauw of IFPRI, Livia Bizikova of IISD, and Francine Picard and Carin Smaller of Shamba Centre for Food and Climate during the policy seminar on How USD 10 billion can transform food systems in Ethiopia, Malawi, and Nigeria: Report launch on March 16, 2023.